Exosomal miR‐3131 derived from endothelial cells with KRAS mutation promotes EndMT by targeting PICK1 in brain arteriovenous malformations. (31st January 2023) - He, Qiheng; Huo, Ran; Wang, Jie; Xu, Hongyuan; Zhao, Shaozhi; Zhang, Junze; Sun, Yingfan; Jiao, Yuming; Weng, Jiancong; Zhao, Jizong; Cao, Yong
Abstract: Aims: To explore the underlying mechanism by which low‐frequency KRAS mutations result in extensive EndMT occurrence. Methods: Exosomes derived from primarily cultured brain arteriovenous malformation (bAVMs) and human umbilical vein endothelial cells (HUVECs) transfected with KRAS G12D, KRAS WT, or KRAS NC lentiviruses were isolated, and their effects on HUVECs were identified by western blotting and immunofluorescence staining. The expression levels of exosomal microRNAs (miRNAs) were evaluated by miRNA microarray, followed by functional experiments on miR‐3131 and detection of its downstream target, and miR‐3131 inhibitor in reversing the EndMT process induced by KRAS G12D ‐transfected HUVECs and bAVM endothelial cells (ECs) were explored. Results: Exosomes derived from KRAS G12D bAVM ECs and KRAS G12D ‐transfected HUVECs promoted EndMT in HUVECs. MiR‐3131 levels were highest in the exosomes of KRAS G12D ‐transfected HUVECs, and HUVECs transfected with the miR‐3131 mimic acquired mesenchymal phenotypes. RNA‐seq and dual‐luciferase reporter assays revealed that PICK1 is the direct downstream target of miR‐3131. Exosomal miR‐3131 was highly expressed in KRAS G12D bAVM exos compared with non‐KRAS‐mutant bAVM exos or HUVEC exos . Finally, a miR‐3131 inhibitor reversed EndMT in HUVECs treated with exosomes or the supernatant of KRAS G12D ‐transfected HUVECs and KRAS G12D bAVM ECs. Conclusion: Exosomal miR‐3131 promotes EndMT in KRAS‐mutant bAVMs, and miR‐3131 might be a potential biomarker and therapeutic target in KRAS G12D ‐mutant bAVMs. Abstract : To explore the underlying mechanism by which low‐frequency KRAS mutations result in extensive EndMT occurrence, exosomes were derived from primarily cultured bAVM and HUVECs transfected with KRAS G12D, KRAS WT, or KRAS NC lentiviruses, and their effects on HUVECs were identified by western blotting and immunofluorescence staining. MiR‐3131 levels were highest in exosomes of KRAS G12D ‐transfected HUVECs, and HUVECs transfected with miR‐3131 mimic acquired mesenchymal phenotypes. RNA‐seq and dual‐luciferase reporter assays revealed that PICK1 is the direct downstream target of miR‐3131. Exosomal miR‐3131 was highly expressed in KRAS G12D bAVM exos compared with non‐KRAS‐mutant bAVM exos or HUVEC exos . Finally, miR‐3131 inhibitor reversed the EndMT in HUVECs treated with exosomes or supernatant of KRAS G12D ‐transfected HUVECs and KRAS G12D bAVM ECs.